2007
DOI: 10.1158/0008-5472.can-06-2184
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rituximab-Resistant Lymphoma Clones with Altered Cell Signaling and Cross-Resistance to Chemotherapy

Abstract: Immunotherapy with rituximab (chimeric anti-CD20 monoclonal antibody, Rituxan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
114
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 48 publications
9
114
1
2
Order By: Relevance
“…Lymphoma cells may become resistant by decreased expression of CD20 antigen, or they may also activate antiapoptotic signal transduction pathways, which Immunotherapy of NHL with Bi20 and DLI R Buhmann et al renders these cells resistant to chemotherapy. 19,20 Host factors involve effector cells of antibody-dependent cellular cytotoxicity and the reticulo-endothelial system removing antibody-loaded cells. 18 These functions may be defective;…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoma cells may become resistant by decreased expression of CD20 antigen, or they may also activate antiapoptotic signal transduction pathways, which Immunotherapy of NHL with Bi20 and DLI R Buhmann et al renders these cells resistant to chemotherapy. 19,20 Host factors involve effector cells of antibody-dependent cellular cytotoxicity and the reticulo-endothelial system removing antibody-loaded cells. 18 These functions may be defective;…”
Section: Discussionmentioning
confidence: 99%
“…However, they can be used as potent agents to bypass drug resistance along with other antitumor agents that primarily act through classical apoptosis. A study in this line suggests that resveratrol is an ideal candidate agent to enhance the apoptotic potential of antitumor agents like TRAIL and paclitaxel (55,56). More preclinical studies are needed to clarify whether 50 M concentration required for the desired biological effect can be achieved in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…46 Several studies have shown that resistant cells display constitutive hyperactivation of the survival pathways NFκB and ERK1/2, leading to overexpression of Bcl-2, Bcl-2-related gene and Mcl-1. 8 In the in vivo resistant RL model, Bcl-X L was also found more highly expressed in rituximab-resistant cells. 28 This confirms the recent results obtained in vitro by Jazirehi et al 8 showing that the phenotype of resistant cells to rituximab may be associated with a higher expression of Bcl-X L .…”
Section: Parameters Correlated With Rituximab Activity and Resistancementioning
confidence: 96%
“…8 In the in vivo resistant RL model, Bcl-X L was also found more highly expressed in rituximab-resistant cells. 28 This confirms the recent results obtained in vitro by Jazirehi et al 8 showing that the phenotype of resistant cells to rituximab may be associated with a higher expression of Bcl-X L . Moreover, we found an overexpression of YY1, a negative regulator of Fas and Trail receptor DR5 expression, that can inhibit apoptosis.…”
Section: Parameters Correlated With Rituximab Activity and Resistancementioning
confidence: 96%
See 1 more Smart Citation